Combined effects of nanoplastics and heavy metal on antioxidant parameters of juvenile tri-spine horseshoe crabs - Arif, Iqra; Shang, Yueyong; Zhang, Caoqi; Khan, Fahim Ullah; Tan, Kian Ann; Waiho, Khor; Wang, Youji; Kwan, Kit Yue; Hu, Menghong (Frontiers in Marine Science, 2022)
Juvenile tri-spine horseshoe crabs (Tachypleus tridentatus) were exposed to determine the effects of single and combined stresses of polystyrene nanoplastics (nano-PS) and heavy metal (Cu2+) on antioxidant enzyme parameters. The juveniles were exposed to a 21-day 100-nm polystyrene concentration (104 particles l-1) and a concentration of Cu2+ (10 µg l-1) followed by a recovery period of 7 days. The in vivo antioxidant activity for whole horseshoe crab was analyzed. The results revealed that all antioxidant parameters, i.e., superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), malondialdehyde (MDA), and lipid peroxidation (LPO), showed both increased and decreased levels in different experimental groups of horseshoe crabs having different experimental conditions compared to the control group at three time points, i.e., on days 7, 14, and 21. Similarly during the recovery period, SOD, CAT, and MDA showed decreased levels in all experimental groups, while GSH and LPO showed increased levels in all experimental groups of horseshoe crabs under the influence of different experimental conditions of nanoplastics and heavy metals compared to the control group on day 28. These results showed that the exposure of nano-PS and Cu2+ had precise effects on juvenile horseshoe crabs. Integrated biomarker responses showed that nano-PS and Cu2+ had adverse effects on juvenile horseshoe crabs. By principal component analysis, the potentially toxic effects of nano-PS and Cu2+ on horseshoe crabs were obtained.